Analisis Kepuasan Pengujung Berdasarkan Tourist Experience ke Daerah Istimewa Yogyakarta - Tarandhika Tantra; Heppy Millanyani; Ilham Meidarlis Yefri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Indonesia is a beautiful country with a variety of interesting tourist destinations. The government developed 10 New Bali in various places in Indonesia to align with regional countries. Yogyakarta is an iconic destination and attracts tourists. In order for Yogyakarta to compete with the destinations of 10 New Bali, research needs to be done to find out how the level of satisfaction of tourists in Yogyakarta based on the visiting experience and know what factors must be improved to be able to move. This study uses quantitative methods with data collection techniques using questionnaires to 385 respondents who are tourists of Yogyakarta. Data processing techniques use Importance Performance Analysis and Customer Satisfaction Index to Tourist Experience. Importance Performance Analysis to determine what aspects and indicators should be improved performance in the Yogyakarta tourism sector. At the same time, the Customer Satisfaction Index to find the level of satisfaction of Yogyakarta tourists. From the analysis of data conducted, it can be known that the satisfaction rate of tourists of Yogyakarta Special Region based on Tourist Experience is 84.9%. Indicators with the most satisfactory performance are hedonistic, and indicators with less satisfactory performance are relational. Based on the results of this study, it is expected that Yogyakarta stakeholders provide education and socialization to the community to interact and communicate better with tourists